Desert Christians: An Introduction to the Literature of Early Monasticism. By William Harmless, SJ - Rich, A. D. (The journal of theological studies, 2007)
In his book Harmless sets out to provide his readers with an introduction to the ‘literature of and about desert Christians’, limiting himself to Egypt between the years 300 and 451; that is, between Antony the Great's ‘public career’ and the Council of Chalcedon. In a clear, easy, and accessible style he achieves his aim and in doing so provides his readers with a comprehensive overview and the resources to extend their studies., The book consists of thirteen chapters in five parts. In the first part Harmless describes some of the general and religious background to fourth- and fifth-century Egypt, which helps to place what follows in a broader context.